FOBIA LAKI-LAKI TOKUJIRA AOI PADA MANGA OOKAMI SHOUNEN WA KYOU MO USO WO KASANERU KARYA NAMO - I Putu Gede Aditya Djanardhana; Anak Agung Ayu Dian Andriyani; Ni Luh Gede Meilantari (Universitas Negeri Padang, 2022)
This study examines the phobia phenomenon on character Tokujira Aoi from manga Ookami Shounen wa Kyou mau Uso wo Kasaneru created by namo. The reason for this study is because, amongst the character with phobia in any anime or manga, Tokujira Aoi is one of androphobia character that not using any violence nor passive-aggressive behaviour toward the subject of her fear, which is male. Therefore, the purpose of the study of this study is to examine how reaction of androphobia occurs on Tokujira Aoi. The data source of this study is using the dialogues between Tokujira Aoi and other characters on manga Ookami Shounen wa Kyou mau Uso wo Kasaneru. Reading and note-taking procedures are used in this study, which also utilized a qualitative descriptive analysis method. The data analysis presentation is by using informal method which the data presented by word-by-word descriptive explanation. The result on this study are concluded that androphobia phenomenon on Tokujira Aoi is classified a specific phobia. Tokujira Aoi has two reaction regarding her fear of man, which are physical and emotional reaction, that caused by trauma.